#### Question

Using truth table show that – (p → – q) ≡ p ∧ q

#### Solution

– (P → – q) ≅ P ∧ q

=`(e^x/(2e^y))=1/2[e^(x-y)]`

`dy/dx=1/2[e^x+e^y]`

Truth table

P (1) | q(2) | -q(3) | p→-q (4) | -(p→-q)(5) | p^q(6) |

T | T | F | F | T | T |

T | F | T | T | F | F |

F | T | F | T | F | F |

F | F | T | T | F | F |

From the truth table, we get 5th and 6th columns are

identical

∴-(p→-q)≅ p∧q

Is there an error in this question or solution?

#### APPEARS IN

Solution Using truth table show that – (p → – q) ≡ p ∧ q Concept: Increasing and Decreasing Functions.